PENERAPAN METODE WATERFALL UNTUK PENYAJIAN PUBLIKASI INDUSTRI PENGOLAHAN LOGAM BERBASIS WEBGIS DI NAGARI SUNGAI PUA - afifu rahman; Triyatno Triyatno (DEPARTEMEN GEOGRAFI FIS UNP, 2019)
The purpose of this research is. 1) mapping the distribution pattern of the metal processing industry in Nagari Sungai Pua. 2) publish the profile and potential of the metal processing industry in Nagari Sungai Pua using a WebGIS based geographic information system. This type of research is quantitative descriptive. In analyzing the distribution pattern of the metal processing industry, the method used is the Nearest Neighborhood analysis method and the method used in building WebGIS is the waterfall method The result of this study are: 1) the distribution pattern of the metal processing industry in Nagari Sungai Pua is random with a T index value of 0,884269. 2) publication related to the profile and potential of the metal processing industry in Nagari Sungai Pua can be accessed using WebGIS which has been successfully build using the waterfall method with the domain address http://webgisindustrisungaipua.000webhostapp.com. This WebGIS presents information about the metal processing industry in Nagari Sungai Pua which is presented in the form of maps containing data ranging from the distribution of metal processing industries, profiles and industrial potential that can be seen by the public so that information related to this industry can be accessed easily.